Implementation of Information And Communication Technology Can Increase Taxpayer Compliance In Reporting PPH 21 - Ayu Wandika Putri Utami; Dwi Astuty Arfah; Yusri Karmila; Arnold Sau (Journal of Economy, Accounting and Management Science (JEAMS), 2024)
This research aims to explore how the implementation of ICT can increase taxpayer compliance in reporting PPh 21 in South Sulawesi Province. By understanding the role and benefits of ICT, it is hoped that effective strategies can be found that can be implemented by several companies in order to increase tax compliance. The method used in this research is qualitative research which examines problems in depth using a non-statistical approach. framework of thought derived from thoughts and literature studies, expert opinions and other sources relevant to the topic of individual taxpayer compliance in reporting PPh 21 in South Sulawesi Province.The results of research conducted show that the implementation of ICT can increase taxpayer compliance in reporting PPh 21 in South Sulawesi Province, which is still not in line with the tax revenue target in 2023. It is still necessary to increase PPh 21 tax compliance by utilizing the role of Information and Communication Technology to significantly increase taxpayer compliance in reporting PPh 21 in Indonesia. In increasing taxpayer compliance in reporting PPh 21, information and communication technology has played an important role. There is a great need for taxpayer awareness regarding the use of e-filing, e-SPT, e-Invoice application, Tax Corner, and consultation and education so that it can help increase taxpayer compliance. Therefore, the government must continue to improve the convenience and quality of tax services to increase taxpayer compliance effectively. Efficiency of the reporting process, increasing knowledge and awareness of taxpayers, as well as reducing operational costs due to the use of ICT. However, to achieve optimal results in taxpayer compliance in South Sulawesi Province, it is necessary to provide adequate training to the community and overcome the challenges of technological adaptation. Such implementation requires support from management, investment in technology infrastructure, and ongoing training.